1997
DOI: 10.2307/1161183
|View full text |Cite
|
Sign up to set email alerts
|

Spirit media: the electronic media and Islam among the Dyula of northern Côte d'Ivoire

Abstract: In 1973 the Muslim Dyula of northern Côte d'Ivoire, in their quarter of Korhogo town or in the villages, listened to the radio and might occasionally see an Italian ‘western’ at the cinema. Television was an exotic rarity; cassettes were a novelty. By 1984 television was ubiquitous; households that had not been interested in radio were now enthusiastic about watching television in the evening. Cassettes had become even more common than radios, and tapes were pirated and copied. The shift from radio and film to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(10 citation statements)
references
References 4 publications
0
7
0
3
Order By: Relevance
“…La plus grande accessibilité des médias a ouvert la voie à de nouvelles figures religieuses, qui n'ont pas nécessairement le profil classique et qui ont mis à profit ces nouveaux outils de communication pour acquérir une légitimité voire une autorité dans la sphère publique (Schulz 2003 ;2006a ;2006b ;Holder 2012 ;Soares 2004 ;2005 ;Launay 1997 ;Masquelier 1999 ;Sounaye 2013). La médiatisation religieuse répond également à une volonté d'accentuer le prosélytisme qui s'inscrit dans le cadre d'une compétition interconfessionnelle, mais aussi -de plus en plus fréquemment -au sein d'une même religion (Krings 2008 ;Hackett 2010 ;Samson 2011 ;Savadogo et Gomez-Perez 2011).…”
Section: Découvrir La Revueunclassified
“…La plus grande accessibilité des médias a ouvert la voie à de nouvelles figures religieuses, qui n'ont pas nécessairement le profil classique et qui ont mis à profit ces nouveaux outils de communication pour acquérir une légitimité voire une autorité dans la sphère publique (Schulz 2003 ;2006a ;2006b ;Holder 2012 ;Soares 2004 ;2005 ;Launay 1997 ;Masquelier 1999 ;Sounaye 2013). La médiatisation religieuse répond également à une volonté d'accentuer le prosélytisme qui s'inscrit dans le cadre d'une compétition interconfessionnelle, mais aussi -de plus en plus fréquemment -au sein d'une même religion (Krings 2008 ;Hackett 2010 ;Samson 2011 ;Savadogo et Gomez-Perez 2011).…”
Section: Découvrir La Revueunclassified
“…In the 1990s, electronic media in Africa played an important role in spreading religious discourse (Launay, 1997;Hackett, 1998). In more recent years, they have gained even more significance as reform discourses have acquired currency and visibility (Schulz, 2007;Sounaye, 2011;Loimeier, 1997), and Muslim public actors rely on small media to advance their agendas (Hirschkind, 2001(Hirschkind, , 2006Schulz, 2007Schulz, , 2012.…”
Section: Production and Circulation: A Community Continuously Mediatedmentioning
confidence: 99%
“…This proposition is supported by the work of Norton (2003), who focused on new media and political reform in Muslim majority countries. In a different continent, Launay (1997) from his research effort in the Ivory Coast observed how television could be used as a direct medium to bring the peaceful and true message of Islam to Muslims and non-Muslims living in that setting. Indeed, contemporary media anthropologists like Lila Abu-Lughod (1993) who has conducted extensive media modelling and reception studies in the Middle East cautions researchers and members of the Muslim public to not automatically assume that the messages, in and of, so-called 'foreign' electronic media will automatically bring about a replacement of traditional Islamic values with Western ones that are usually viewed with suspicion and as incompatible with the Muslim way-of-life.…”
Section: Review Of Current Literature In the Humanities And Social Scmentioning
confidence: 99%